The Interface: Language, Gender and Power - Gyamera, Vera (Journal of Gender and Power, 2019)
Language, gender and power are major concepts in many academic disciplines. These concepts are expressed in different ways by different societies. The interface of these concepts is the focal point of this paper. The paper brings to fore how gender affects language use in the society and how power is demonstrated using language citing examples from African and Western context. The study reveals that, language is used to construct gender in that, we use language to demonstrate and convey what society anticipates from both sexes and power is demonstrated and achieved through language.